2016
DOI: 10.3847/0004-637x/819/2/107
|View full text |Cite
|
Sign up to set email alerts
|

Accretion Flow Dynamics of Maxi j1836-194 During Its 2011 Outburst From Tcaf Solution

Abstract: We study transient Galatic black hole candidate MAXI J1836-194 during its 2011 outburst using RXTE/PCA archival data. 2.5-25 keV spectra are fitted with Two Component Advective Flow (TCAF) model fits file as an additive table local model in XSPEC. From TCAF model spectral fits, physical parameters such as Keplerian disk rate, sub-Keplerian halo rate, shock location and compression ratio are extracted directly for better understanding of accretion processes around the BHC during this outburst. Low frequency qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 36 publications
1
67
0
Order By: Relevance
“…In our recent study of MAXI objects (MAXI J1659-152, MAXI J1836-194, MAXI J1543-564), we observed that if we allow mass of the BHCs to vary in a small range while fitting spectra with TCAF solution, model normalization (which is a fraction 1 4πD 2 sin(i), where 'D' is the source distance in units of 10 kpc and 'i' is the disk inclination angle) comes out roughly in a narrow range 11,12 . The uncertainty in the normalization is reflected in the uncertainly in the mass.…”
Section: Mass Estimation Of Unknown Bhcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent study of MAXI objects (MAXI J1659-152, MAXI J1836-194, MAXI J1543-564), we observed that if we allow mass of the BHCs to vary in a small range while fitting spectra with TCAF solution, model normalization (which is a fraction 1 4πD 2 sin(i), where 'D' is the source distance in units of 10 kpc and 'i' is the disk inclination angle) comes out roughly in a narrow range 11,12 . The uncertainty in the normalization is reflected in the uncertainly in the mass.…”
Section: Mass Estimation Of Unknown Bhcsmentioning
confidence: 99%
“…Recently, after the inclusion of TCAF solution in HEASARC's spectral analysis software package XSPEC as a local additive table model (7,8,9,10,11, hereafter DCM14, DMC15, DMCM15, MDC14, JDCMM16 respectively), which requires only five physical parameters (including mass) to fit a spectrum from a BHC. An accurate picture of the accretion flow dynamics around several transient BHCs (e.g., H 1743-322, GX 339-4, MAXI J1659-152, MAXI J1836-194) during their X-ray outbursts was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study of MAXI objects (MAXI J1659-152, MAXI J1836-194, MAXI J1543-564), we observed that if we allow mass of the BHCs to vary in a small range while fitting spectra with TCAF solution, model normalization (which is a fraction 1 4πD 2 sin(i), where 'D' is the source distance in units of 10 kpc and 'i' is the disk inclination angle) comes out roughly in a constant 9,11 . This allows us to predict most preferable range of the mass of an unknown BHC, which could also be verified from POS model 2,3,12-14 fitted QPO frequency evolutions during rising and declining phases of the outbursts.…”
Section: Mass Estimation Of Unknown Bhcsmentioning
confidence: 99%
“…In general, these objects show different spectral states (hard (HS), hard Intermediate (HIMS), Soft Intermediate (SIMS) and Soft (SS), and low frequency quasi-periodic oscillations (QPOs) in some of these states (1,2,3). The spectral evolution of states in BH transients are also found to be associated with different branches of a physical hysteresis diagram, accretion rate ratio vs X-ray intensity (ARRID; see, Jana et al 4 ). Different branches of this diagram are found to be related with different observed spectral states.…”
Section: Introductionmentioning
confidence: 99%